Long-Term Grazing Exclusion Reduces Species Diversity but Increases Community Heterogeneity in an Alpine Grassland - Song, Shanshan; Zhu, Jiangling; Zheng, Tianli; Tang, Zhiyao; Zhang, Fan; Ji, Chengjun; Shen, Zehao; Zhu, Jianxiao (Frontiers in Ecology and Evolution, 2020)
Extensive grazing activity is threatening the alpine grassland of the Qinghai-Tibetan Plateau. Evidence has shown that grazing exclusion may change the composition, structure, and functions of grassland ecosystems. However, such effects depend on the intensity and duration of exclusion. We explored the effects of short-term (2 and 4 years) and long-term (9 and 11 years) grazing exclusion on plant height, coverage, and diversity and community heterogeneity in the alpine grassland of the Qinghai-Tibetan Plateau. We found no difference in plant diversity between short-term grazing exclusion and control. However, long-term grazing exclusion reduced species richness and increased the Simpson dominance index. This decrease in plant species richness was mainly attributable to the decrease in common species richness (defined as species with a relative coverage of 1∼5%). In addition, community heterogeneity (coefficient of variation, CV) was significantly higher in long-term grazing exclusion than in controlled plots. Structural equation modeling (SEM) demonstrated that long-term grazing exclusion increased the community heterogeneity mainly by reducing species diversity. These results suggest that the effects of grazing exclusion on the composition, structure, and community spatial heterogeneity of the alpine grassland ecosystem are dependent on exclusion duration. Grazing activity may maintain the high biodiversity and community stability of the alpine grassland in the harsh environment of the Qinghai-Tibetan Plateau.